Seasonal emergence of swine erysipelas in hilly state Nagaland, Northeast India - Nagendra Nath Barman, Debojyoti Borkotoky , Biswajyoti Borah; Anjan Jyoti Nath , Papiya Das, Durlav Prasad Borah (African Journal of Pig Farming, 2020)
Seasonal outbreaks of swine erysipelas have been reported in back yard pig farms in the Phek district of Nagaland, India. The alpha haemolytic isolate of Erysipelothrix rhusiopathiae was recovered on blood agar from the clinical samples. The organisms were confirmed microscopically, biochemical analysis as well as by polymerase chain reaction (PCR) amplification of 16S rRNA gene and sequence analysis. These Nagaland isolates (KT160358, KT160359) were closely related to the type spp. E. rhusiopathiae in phylogenetic analysis and forms the same clad with Chineese isolates of swine and murine origin indicating an epidemiological link. The isolates were found to be most sensitive to oxytetracycline and responded to treatment. Swine erysipelas occurred in Phek district in a season due to sudden change of weather and temperature. Pigs exposed to such predisposing factors probably favoured to propagation of already persisted organisms in pigs. This is the first confirmed case of E. rhusiopathiae infection from the NE states of Nagaland, India.